2021
DOI: 10.3389/fphar.2021.666047
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-dependent alpha1-Adrenoceptor Antagonism and Inhibition of Neurogenic Smooth Muscle Contraction by Mirabegron in the Human Prostate

Abstract: Introduction: Mirabegron is available for treatment of storage symptoms in overactive bladder, which may be improved by β3-adrenoceptor-induced bladder smooth muscle relaxation. In addition to storage symptoms, lower urinary tract symptoms in men include obstructive symptoms attributed to benign prostatic hyperplasia, caused by increased prostate smooth muscle tone and prostate enlargement. In contrast to the bladder and storage symptoms, effects of mirabegron on prostate smooth muscle contraction and obstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 61 publications
0
5
1
Order By: Relevance
“…Additionally, during its regulatory submission, it was also indicated that this drug potentially antagonises α 1 -adrenoceptors (U.S. Food and Drug Administration 2012 ). In our ureteral study, mirabegron, at 10 μM, also decreased maximum contractions which was not observed in the urethra (Alexandre et al 2016 ) or prostate (Huang et al 2021 ). Due to this decrease in maximum contractions, we could only calculate apparent pA 2 values using shifts at the lower part of the concentration curves.…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…Additionally, during its regulatory submission, it was also indicated that this drug potentially antagonises α 1 -adrenoceptors (U.S. Food and Drug Administration 2012 ). In our ureteral study, mirabegron, at 10 μM, also decreased maximum contractions which was not observed in the urethra (Alexandre et al 2016 ) or prostate (Huang et al 2021 ). Due to this decrease in maximum contractions, we could only calculate apparent pA 2 values using shifts at the lower part of the concentration curves.…”
Section: Discussioncontrasting
confidence: 40%
“…Our agonist concentration response studies showed that the presence of mirabegron, at 1 μM and higher, was capable of antagonising phenylephrine-induced contractility. This is not surprising, as previous studies have reported that similar concentrations of mirabegron antagonises other receptors including α 1 -adrenoceptor stimulation in the urethra (Alexandre et al 2016 ) and prostate (Alexandre et al 2016 ; Huang et al 2021 ), and muscarinic receptors in the pig and human detrusor (Maki et al 2019 ; Yamada et al 2021 ). Additionally, during its regulatory submission, it was also indicated that this drug potentially antagonises α 1 -adrenoceptors (U.S. Food and Drug Administration 2012 ).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…It has been speculated that such adverse effects are related to a phenyl ethanolamine backbone, which is present in mirabegron and several other β 3 -AR agonists and may cause indirect sympathomimetic activity [197]. Moreover, at least mirabegron has additional off-target effects such as antagonism at α 1adrenoceptors [198][199][200]. Such off-target effects were neither reported nor are expected for the β 3 -AR agonists with other chemical backbones.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…H9c2 cells with 60-70% confluency were serum starved and were then treated with angiotensin II (Ang II) (600 nM), mirabegron (10 µM), Compound C (10 µM), and/or mdvid1 (20 µM) simultaneously as stated in the figures for 24 hours. The doses of the treatments were based on published studies (17)(18)(19)(20). The cells were harvested for immunoblotting.…”
Section: Cardiomyocyte Hypertrophy Model Of H9c2 Cellsmentioning
confidence: 99%